The works of Jacob Behmen, the Teutonic theosopher: to which is prefixed, the life of the author - Böhme, Jakob (Printed for M. Richardson in Pater-noster Row, 1764)
v. 1. The aurora. The three principles -- v. 2. The threefold life of man. The answers to forty questions concerning the soul. The treatise of the incarnation. The clavis, or, An explanation of some principal points and expressions in his writings -- v. 3. The mysterium magnum, or, An explanation of Genesis. Four tables of divine revelation -- v. 4. Signatura rerum. Of the election of grace, or, Of God's will towards man, commonly called predestination. The way to Christ. A discourse between a soul hungry and thirsty after the fountain of life, the sweet love of Jesus Christ; and a soul enlightened. Of the four complexions. Of Christ's testaments, baptism, and the supper.